Impacts of green manure on crop yield, nitrogen leaching and nitrous oxide emissions in sandy and clay soil lysimeters - Regina, Kristiina; Känkänen, Hannu; Singh, Pooja (Scientific Agricultural Society of Finland, 2021)
We compared wheat yield, losses of nitrogen (N) in leaching and gaseous losses as nitrous oxide (N2O) in silt and sand soil lysimeters. The studied cultivation systems were based on mineral fertilizer or mineral fertilizer together with clover green manure mulched at three different time points (August, October or May) before sowing of the main crop (either winter or spring wheat). Replacing 50–60% of mineral fertilizer N with green manure from a mixture of three clover species did not compromise crop yield of winter or spring wheat. The results suggest that mulching of the green manure in the spring succeeding its sowing is the most beneficial practice with respect to environmental impacts. Total N leaching was higher from sandy soil than from silt loam whereas emissions of N2O were higher from the silt soil. Residual N from the clover biomass did not lead to an increase in leaching losses of N during the growing season or one year from the harvest. However, the residual N can be a source of high N2O emissions during the winter period in boreal climatic conditions.
Keywords: cover crop; fertilizer; nutrient management; cereal; vilja; clovers; apilat; lannoitteet